Early rhythm-control therapy in patients with atrial fibrillation: a nationwide cohort study. (14th October 2021) - Chao, T; Chan, Y.H; Lip, G.Y.H; Chen, S.A
Abstract: Background: In the Early Treatment of Atrial Fibrillation for Stroke Prevention Trial (EAST-AFNET 4), early rhythm control was associated with better clinical outcomes for patients with atrial fibrillation (AF). However, the intervention arm had more structured and regular followup, and whether the better outcomes of patients assigned to rhythm control were solely due to "early" intervention or because of more regular and structured follow up was unclear. Purpose: We aimed to investigate whether the findings of the EAST trial are applicable to the "real world" clinical setting, where a less structured management protocol is operated. Methods: From 2001 to 2016, 301, 064 newly-diagnosed AF patients were identified from Taiwan National Health Insurance Research Database. Among these patients, 62, 649 AF patients receiving antiarrhythmic drugs or catheter ablation within 1 year after AF being diagnosed (similar to the timing definition of the EAST-AFNET 4 trial) were categorized as the early rhythm control group, and the remaining 238, 415 patients were defined as usual care group. Risk of clinical events were compared between 2 groups. Results: Compared to usual care, early rhythm control was associated with a lower adjusted risk of ischemic stroke (aHR 0.771, 95CI 0.751–0.792; p<0.001), heart failure (aHR 0.851, 95% CI 0.806–0.891; p<0.001), acute myocardial infarction (aHR 0.915, 95% CI 0.877–0.955; p<0.001), mortality (aHR 0.794, 95% CI 0.782–0.806; p<0.001) and composite adverse events (aHR 0.823, 95% CI 0.813–0.834; p<0.001) (Figure). Compared to usual care, the lower risks of ischemic stroke (aHR 0.746, 95% CI 0.717–0.775), heart failure (aHR 0.819, 95% CI 0.798–0.841), mortality (aHR 0.777, 95% CI 0.759–0.795) and composite adverse events (aHR 0.802, 95% CI 0.787–0.818) associated with early rhythm control were even more evident when performed early (<3 months) than later periods (3–6 months, 7–9 months and 10–12 months; pint <0.001). Principal results were generally consistent for majority of subgroups studied and among the cohort after the propensity matching. Conclusions: In this nationwide cohort study, early rhythm control therapy was associated with a lower risk of adverse events than usual care among patients with early AF. Outcomes were even better with earlier (<3 months) intervention. Funding Acknowledgement: Type of funding sources: None.